Carbon pricing, technology transition, and skill-based development - Kirill Borissov; Lucas Bretschger; Alexandra Vinogradova (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
We analyze the impact of carbon prices on human capital accumulation, sectoral change, and economic growth. In our framework output is produced with dirty and/or clean technologies using skilled and unskilled labor as inputs. Carbon policy affects technology selection which transmits incentives for human capital formation. We show that a temporary policy may be sufficient for a transition to a clean economy and that such a policy also stimulates economic growth. Moreover, in the presence of inter-country knowledge spillovers, a carbon policy in the North helps human capital formation in the South and induces South's transition to the clean steady state.
Keywords: Q43; O47; Q56; O41; 330; Carbon pricing; education; clean and dirty technologies; temporary policies